Conceptual Politics of the Development of Identity of Political Science in the Future - Yimaon, Chatchaphanu; Kanchom, Wanlada; Suwannagoot, Patcharaporn (Interdisciplinary Academic and Research Journal, 2023)
The work of political scientists since the inception of the field in the United States is the work of creating an identity in the study of politics with the Scientific Method, officially known as “Behavioral Science”. This work is the quality that makes political science different from other disciplines. After political education has transitioned into the post-behavioral science era until now, for a total of 53 years, political science education is still classified in the former era, that is, there is no identity of the disciplines that are unified like the behavioral science era. Thus, the research paper aimed (1) to review and analyze the form of the developmental Identity in Political Science, and (2) forecast the identity of political science in the future. The scope of this research has been carried out from 1950-2022 and reviewed the status of knowledge in Political Science. The research methodology was documentary research to collect the key informant’s political scientists who published a status assessment and provided an oral history of political science. Data analysis and management by conceptual politics. The results showed that a form of identity-building political science is a political system in which the environment influences the input of demands into the planning process and coming out as a result to be the development of identity in the era of behavioral sciences or post-behavioral sciences and rational choice theory. Therefore, the future of the identity of political science will predict that the identity of political science will form when approaches are composed of simplicity, broad application, formalizable, familiarity, and marginality.